Factors influencing medication adherence among hypertensive patients in primary care settings in Central Vietnam: A cross-sectional study - Ho Anh Hien; Nguyen Minh Tam; Huynh Van Minh; Tran Binh Thang; Le Phuoc Hoang; Stefan Heytens; Dirk Devroey; Hoang Anh Tien (PLoS ONE, 2025)
Background Medication adherence plays a crucial role in effectively managing hypertension, a significant public health concern, especially in regions like Central Vietnam. This study aimed to assess medication adherence levels among hypertensive patients in primary care settings and explore the factors influencing adherence within this specific population. Methods We conducted a cross-sectional study to evaluate medication adherence and its determinants among individuals with hypertension in Central Vietnam. Medication adherence was assessed using the 5-item version of the Medication Adherence Report Scale self-report. We collected data on the demographics, medical history, lifestyle, hypertension knowledge, along with the patient beliefs and perceptions about hypertension. Logistic regression analysis was employed to identify the key factors associated with their medication adherence. Results Our study revealed that only half of the hypertensive patients adhered to their prescribed medication regimens. Several factors significantly influenced their medication adherence, including age, ethnicity, educational level, home blood pressure monitoring, healthy diet, time since hypertension diagnosis, hypertension knowledge, and patient beliefs. According to the logistic regression analysis, a healthy diet and patient beliefs emerged as primary predictors of medication adherence. Patients who strongly believed in the necessity of medication demonstrated better adherence, while concerns about overuse and harm were linked to lower adherence levels. Conclusions This study highlighted the suboptimal levels of medication adherence among hypertensive patients in primary care settings in Central Vietnam. It underscored the urgent need for tailored interventions to address this issue. For the sake of better medication adherence, healthcare providers were suggested to prioritize patient education, address patient beliefs and concerns about medication, and promote the practice of home blood pressure monitoring.